INSTITUTIONAL MEMETICS: METONYMY, LIMINALITY, AND DIGITAL RELIGION - Burroughs, Benjamin (AoIR Selected Papers of Internet Research, 2015)
The rise of memetic culture in digital media is a growing source of popular culture and academic research. Moving from /b/ board insider knowledge to broader cultural adoption, this paper theorizes the intervention of institutions into the production and circulation of memes as a part of a third wave of memetic culture. While studies on memes have emphasized the push of participatory culture into everyday life, this research on religious institutional memes contributes to an emergent vein of digital religion scholarship focused on institutional authority. In an analysis of the Mormon ‘doubt your doubts’ meme as liminal and metonymic, we theorize religious memetics as a space for the reconnection of the everydayness of religious practice to institutions, which boils down meaningful moments of faith into facile, non-threatening avenues for sharing religion. While this is beneficial for institutions, the reflexive and metonymic function of religious memes ruptures routine, offering participants momentary pauses from the demands of orthodox religious life; a cathartic release and recalibration within everyday religious practice. Implications on corporate branding, public relations, and the pitfalls of publication are discussed.